Grain Growth Behavior of Alumina in Zirconia-Toughened Alumina (ZTA) Ceramics During Pressureless Sintering - Yi Zhao; Jiang Deng; Wen Li; Jianhong Liu; Wenjie Yuan (Crystals, 2025)
The primary grain size, sintering conditions, and admixtures have a significant impact on the grain growth of alumina ceramics. Three kinds of alumina powders with varying grain sizes and zirconia nanoparticles were selected and configured into five compositions of zirconia-toughened alumina (ZTA) ceramics. As-received granules were used to sinter bulk ceramics at temperatures of 1520 °C, 1600 °C, and 1680 °C for durations of 0.5–2 h, respectively. The average grain sizes of alumina in ZTA ceramics were studied as a function of the sintering temperature, time, and particle size of raw materials. The results demonstrated that the addition of nano alumina led to a slight reduction in the grain size of alumina and a more uniform grain size distribution. The incorporation of nano zirconia (15 wt.%) resulted in the concentration of zirconia among the alumina grains, effectively inhibiting grain growth and resulting in a significant reduction in the average grain size of alumina from 11.73 to 5.63 μm after sintering at 1600 °C for 1 h.